Samson : hero or fool? : the many faces of Samson - Eynikel, Erik. (Themes in Biblical Narrative, 2014)
Samson is a peculiar character. He is the most powerful of the Israelite judges and three whole chapters in the book of Judges are allocated to him. Yet he demonstrates many weaknesses, not least for the charms of women. In the international conference "Samson: Hero or Fool?" organised at the University of Nijmegen in April, 2008, the texts of Judges 16-18 were studied from different perspectives, investigating how the complex character of this (anti)hero lived on in various ways in the later traditions about him. The contributions discuss also the reception history of the Samson traditions in later Jewish, Christian and Islamic literature, as well as his representation in figurative and performing arts